Impact Assessment of Invasive Alien Plant Species on Chimdi (Barju) Lake of Eastern Nepal - Das, Bishnu Dev; Sharma, Upasana (Darul Yasin Al Sys, 2025)
The present study has been carried out to evaluate the impact assessment of invasive alien plant species on Chimdi Lake using focus group discussion method. Chimdi (Barju) Lake is an important wetland in Eastern Nepal, faces ecological challenges due to the rapid spread of invasive alien plant species. Assessing the impact of these species is essential to understand their effects on the lake's biodiversity and ecosystem services and to develop effective management strategies for the conservation of the lake. The lake was found to be dominated by two aquatic IAPS, Pontederia crassipes followed by Ipomoea carnea. Additionally, eight other terrestrial IAPS (Ageretina adenophora, Chromolaena adorata, Lantana camara, Mikania micrantha, Mimosa pudica, Senna occidentalis., Senna tora, and Xanthium strumarium) were also recorded from the lake. Apart from these, there were several more macrophytes and hydrophytes, such as Nelumbo nucifera, Nymphaea alba, Ipomoea aquatica, etc., which created a thick layer of peat over lake water. These IAPS characteristics encourage growth and cover in water bodies, which block sunlight, change the chemistry of the water, and also reduce the habitat quality of native water animals and plants.